Application of FOSM and Chebyshev’s Theorem Concept to Predict Compressive Strength Attributes of Corncob Ash Embedded Cement Concrete - B S Keerthi Gowda; M S Dakshayini (Computational Engineering and Physical Modeling, 2020)
In the present study the physical and mechanical properties of Corn Cob Ash (CCA) embedded cement concrete of mix proportions 1:1.6:2.6 and water-cement ratios of 0.45 were examined and compared with conventional cement concrete. A total of 96 concrete cubes of size 150 × 150 × 150 mm³ with different percentages by volume of CCA to ordinary Portland cement of grade 30Mpa in the order 0:100, 5:95, 10:90 and 15:85 were cast, tested and their physical and mechanical properties were determined. The specific gravity of the CCA was 3.15. The cubes were cured in a laboratory setup and compressive strength measures of 7, 14, 21, 28, 35, 42 and 56 days were observed. The compressive strength tests on cement concrete by replacing cement with 5% of CCA showed quite satisfactory results at 28days, 35days, 42days and 56days curing period compared to conventional concrete. But 15% CCA replacing for cement did not meet the satisfactory strength attributes. The probability analysis for compressive strength attributes were studied and presented. Chebyshev’s theorem was utilised to find how spread the data is from mean. First order second moment method was used to found mean compressive strength and standard deviations. As the CCA replacement level increased, the compressive strength and workability decreased. However the concrete cubes have gained strength with age. The results indicate that CCA is an adoptable mineral admixture and pozzolan with the substitution level of 5% cement, with no unfavourable consequences for other different attributes of the hardened cement concrete.